Kepadatan dan Persebaran Parmarion pupillaris pada 10 Jenis Sayuran di Desa Dlangu, Kecamatan Trawas, Kabupaten Mojokerto: Density and Distribution of Parmarion pupillaris on 10 Species of Vegetables in Dlangu Village, Trawas District, Mojokerto Regency - Oktavia Pradikaningrum, Novi; Chikmawati, Tatik; Widarto, Tri Heru; Novi (Jurnal Sumberdaya Hayati, 2022)
Vegetables are one of horticultural commodities having a relatively short life cycle. Pest is one of the problems faced in vegetable cultivations. One specie that often attack vegetables is Parmarion pupillaris (Mollusca). It is a semi-slug that has a small bump transparent coat and shell on its back. These semi-slugs are often found eating leaves, stems, flowers and fruit of the vegetables. The aims of the study were to study distribution patterns, density, feeding activity and size distribution of the P. pupillaris in 10 species of vegetables in Dlangu Village, Trawas District, Mojokerto Regency. The observation plots were chosen randomly by determining three plots of each species sized 1m x 1m plot with three replications. Direct observation of feeding activities was conducted at night. Measurement of body length was conducted directly at the time of observation. Data analysis of density and distribution patterns used the quadratic method and Morisita Index. The results of this study showed that the highest P. pupillaris density found in tomato (Solanum lycopersicum), 8.7 ind / m2, while the lowest density was found in corn (Zea mays), 0.5 ind / m2. P. pupillaris found had medium and small sizes. Distribution patterns of semi-slugs based on the Morisita Index is categorized as clump.